Electronic and optical properties of Er-doped Y2O2S phosphors. Issue 43 (14th October 2015) - Pokhrel, M.; Kumar, G. A.; Ma, C.-G.; Brik, M. G.; Langloss, Brian W.; Stanton, Ian N.; Therien, Michael J.; Sardar, D. K.; Mao, Yuanbing
Abstract : Green light emitted from Y2 O2 S:1%Er phosphors after excited with NIR, UV and X-ray sources with emissions spectra under UV and NIR excitations (lower right) and X-ray excitation at different X-ray tube voltages (lower left). Abstract : In this paper, we report a detailed computational and experimental investigation of the structural, electronic and dynamic properties of undoped and Er 3+ -doped Y2 O2 S phosphors by using computational crystal field (CF) calculations and electronic density of states by density functional theory (DFT), combined with optical measurements including excitation spectra, emission spectra from X-ray, ultraviolet and near infrared (NIR) excitations, and quantum yield determination under ultraviolet and NIR excitations. Emission decays and quantum yields of the visible and NIR bands were measured for different Er 3+ doping concentrations in the Er 3+ -doped Y2 O2 S phosphors. Results show that green (550 nm) and red (667 nm) emission intensity and the respective ratio of these emission intensities depend on both the excitation wavelength and the Er 3+ doping concentration. Although the total emission efficiency does not appreciably depend on the excitation wavelength, the excitation wavelength that provided the highest efficiency was found to be 250 nm in these Er 3+ -doped Y2 O2 S phosphors with both 1% and 10% Er doping concentrations.